Improving The Students’ Cognitive Aspects In Oxy Acetylene Welding Course - Bernardus Agus Munadi; Sunaryo Soenarto; Haryo Aji Pambudi (Journal of Educational Science and Technology (EST), 2019)
This study aims at improving learning activities and learning outcomes of cognitive aspects among X grade students of Metal Fabrication Engineering and Manufacturing, Vocational High School (VHS) using Problem-Based Learning (PBL) method. This study used classroom action research, which was conducted in two cycles. Each cycle consisted of four stages, i.e. planning, implementation, observation, and reflection. This study involved one collaborator to assist researchers in implementing PBL and to monitor the learning process. The data collection technique used observation method with checklist and rating scale instrument. The data were analyzed descriptively. The results showed that the PBL implementation method in ignition system learning improve the students’ learning activities with the percentage of 11.20%, the learning activities, in which 29 students were in very high category and 3 students with high category. Also, the learning outcomes of cognitive aspects getting higher to 5.32% consisting of remembering (86.87%), understanding (77.68%), applying (78.77%), analyzing (79.61%), evaluation (77.97%), and creating (79.16%) respectively. Moreover, the students’ learning outcomes raised of which 29 students (91.31%) achieved above the minimum completeness criteria. It means that the PBL model can be used by vocational high teachers as alternative learning process to improve their outcomes of the cognitive aspects.